Cocriação de valor como estratégia de comunicação na sociedade em rede: estudo do programa Cocriando Natura - Dalla Valle, Taisa de Oliveira Ferro (2016)
This dissertation investigates an online co-creation network as a communication strategy and it is delimited to analyze the co-creation of value between organizations and their public as a communication strategy in the network society. The problem that leads the study focuses on the assumption that co-creation in online network enables new forms of interactions and relationships between organizations and their public and it is structured as follows: "How does Natura use an online co-creation network as a communication strategy in the network society?" The general objective of the research is to analyze the co-creation of value by Natura as an organizational communication strategy. The specific objectives are defined as follows: (1) Describing the main digital social media used. (2) Checking the strategic appropriation of an online network for the co-creation of value; (3) Describing the online co-creation network created by Natura; (4) Analyzing the forms of interactions provided by the online co-creation network of Natura s Cocriando Program. The methodological approach of the research consists in the articulated application of different and complementary methods and techniques that seek to investigate how the communication strategies through co-creation in the digital ambience of the researched organization shape up. The course includes the study through non-participant observation in digital social media and in online co-creation network of Natura s Cocriando Program. In addition, there is the indepth interview with the person responsible for the company's innovation management and the asynchronous interview through structured questionnaire with the participants that contributed the most with ideas on Jornada SOU. We used the analytical model structured for the analysis of digital platforms proposed by Proulx (2012) and the interaction blocks proposed by Prahalad and Ramaswamy (2004) so there would have co-creation. From the merger of these two methodological perspectives we created a third model of analysis that includes five categories: the platform's technical architecture; dialogue; user experience, riskbenefit and user contribution. In this context, we found out that the co-creation of value made strategic communication processes between Natura and its public possible. The co-creation network can be considered a complex and unprecedented tool when it comes to structure different stakeholders in network, in order to jointly create ideas through online interactions, aiming at innovation.